The emotional rollercoaster of language teaching - Gkonou, Christina; Dewaele, Jean-Marc 1962-; King, Jim 1974- (Multilingual Matters, 2020)
Foreword / Jane Arnold -- 1. Introduction to the Emotional Rollercoaster of Language Teaching / Christina Gkonou, Jean-Marc Dewaele and Jim King -- 2. The Thrills and Ills of CLIL / Nicole Hofstadler, Kyle Talbot, Sarah Mercer and Anita Lämmerer -- 3. Utilizing the Emotional Labour Scale to Analyse the Form and Extent of Emotional Labour among Foreign Language Teachers in the US Public School System / Kris Acheson and Robert Bruce Nelson -- 4. Theorizing Emotions from a Critical Perspective: English Language Teachers' Emotion Labour When Responding to Student Writing / Sarah Benesch -- 5. 'Opening Pandora's Box': Language Teachers' Dynamic Emotional Experiences of Conducting Action Research / Emily Edwards and Anne Burns -- 6. Resilience in Language Teaching: Adaptive and Maladaptive Outcomes in Preservice Teachers / Achilleas Kostoulas and Anita Lämmerer --
Includes bibliographical references and index
Keywords: Sprachlehrer; Psychische Belastung; Gefühl; Language acquisition / Psychological aspects; Language and languages / Study and teaching / Psychological aspects; Psycholinguistics